Testing the feasibility of a primary-care exercise intervention to prevent and reverse early frailty and build resilience in community-dwelling older adults - Romero-Ortuno, Roman (My University, 2022)
Background: Resistance exercises have been shown to prevent and reverse frailty but their application in clinical practice is low. We wished to test the feasibility of an optimised exercise intervention for mild or pre-frailty in a primary-care setting and inform the design of a definitive randomised control trial. Methods: The intervention was co-designed with eighteen older adults in two group workshops, informed by systematic review and meta-analysis. Eligible patients aged 65+, mildly frail or less, presenting to an Irish primary-care centre over 6 months from January 2020 were invited to participate. They were offered an exercise guide and educational discussion. Demographics, health indicators and frailty scores were recorded. Feasibility was assessed using the Bowen model for acceptability; participation; demand; implementation; practicality; adaptation; integration; expansion; and limited-efficacy. Half of the randomly selected participants were telephoned after one month, and all the participants were called after two to measure effects on adherence. Findings: 94 of 107 eligible people (88%) participated (average age 77, 59 women (63%)). Only 15% had previously considered resistance exercises. The intervention satisfied all Bowen feasibility criteria. At one month, 65% of participants were exercising. At two months, adherence amongst those previously called was higher: 78%. 87% described exercises as ‘very easy’ or ‘somewhat easy’. 66% felt ‘much better’ or ‘slightly better’. Interpretation: Frailty intervention uptake and adherence were high. A single telephone call appeared to help increase adherence. Participants reported meaningful physical and mental health benefits.
PUBLISHED
Keywords: Frailty; Resilience; Feasibility; Primary-care; Exercise; Ageing; Inclusive Society; Age-related disability; Chronic Health Condition; Mobility impairment; Physical disability; Health; Third age/ageing